Geoenvironmental engineering ground contamination : pollutant management and remediation : proceedings of the second conference organized by the British Geotechnical Society and the Cardiff School of Engineering, University of Wales, Cardiff, and held in London on 13-15 September 1999 - Yong, R. N.; Thomas, H. R. (Thomas Telford, 1999)
Geoenvironmental engineering issues are of increasing importance around the world. This international trend is apparent in the UK government's active encouragement of the use of brownfield sites for urban development to ease the pressure on the countryside. This book contains the collected papers from the 2nd Geoenvironmental Engineering Conference.